Fast inter-prediction mode decision algorithm for HEVC. Issue 1 (January 2017) - Huang, Xinpeng; Zhang, Qiuwen; Zhao, Xiaoxin; Zhang, Weiwei; Zhang, Yan; Gan, Yong
Abstract The high efficiency video coding (HEVC) is superior to the previous video coding standards in compression performance, while the computational complexity is introduced simultaneously. The complexity increases mainly due to the novel flexible partitioning scheme that allows the inter-prediction mode partition split via exhaustive rate-distortion optimization (RDO). In this paper, a fast inter-prediction mode decision algorithm is proposed, which contains adaptive threshold determination based on quantization parameter and fast inter-prediction mode partition decision. The proposed algorithm utilizes the edge information of the partition to simplify the RDO and then accelerates coding time of inter-prediction mode decision structure for the original HEVC encoder. The experimental results show that the proposed algorithm can achieve 39.5 % coding time reduction with just 1.97 % bitrate increase on average under random access condition and 35.2 % coding time reduction with just 1.89 % bitrate increase on average under low-delay B condition, compared to the original HEVC encoder.